Foregut mesenchyme contributes cells to pancreatic acini during embryonic development in a chick-quail chimera model. - Teague, W; Jayanthi, N; Lear, P; Johnson, P (2005)
To understand causes of developmental abnormalities of the pancreas, it is essential to understand its normal embryonic development. Current understanding of the development of pancreatic exocrine tissue is that it develops solely from embryonic epithelium, while the role of the surrounding mesenchyme is to signal to this epithelium and form connective tissue. Recent work in our laboratory has shown that pancreatic bud mesenchyme can contribute cells to islets during embryonic development. However, no published studies have investigated in detail whether mesenchyme contributes cells to the exocrine structures of the pancreas. The aim of this study was to investigate whether cells from foregut mesenchyme can contribute to pancreatic acini during embryonic development. Chick-quail chimera recombinant organs were constructed using pancreatic epithelium and mesenchyme from either the pancreas (n=12) or stomach (n=25). These were cultured for 7 days in 3-D collagen gels. The resulting specimens were analysed using morphological criteria and fluorescent immunocytochemistry against pancreatic amylase, insulin, and the quail-specific nucleolar antigen QCPN. Two independent observers determined the origins of acini as either solely epithelial, solely mesenchymal, or of mixed origin. Results are expressed as percentages of total acini identified in each group. Statistical analysis was performed using chi(2) tests (P<0.01 was considered statistically significant). Recombinations of pancreatic epithelium and pancreatic mesenchyme yielded 11 acini, of which 45% were derived from epithelium only, 45% from mesenchyme only, and 10% of mixed origin. Recombinations of pancreatic epithelium and stomach mesenchyme yielded 78 acini, of which 40% were derived from epithelium only, 32% from mesenchyme only, and 28% of mixed origin. When acini with any mesenchymal cellular contribution were considered as a group, there was no significant difference between stomach and pancreatic mesenchymal contribution (P=0.72). This is the first study to demonstrate the cellular contribution of mesenchyme to pancreatic exocrine structures. Our data show that mesenchyme contributes cells to pancreatic acini during development in this model and that mesenchyme derived from stomach and pancreatic sources are both able to form acini.